Dimensionless parameters for ballistic performance evaluation of ceramic-faced bicomponent targets against sharp-nosed projectiles. (March 2023) - Guo, Zherui
Highlights: Ballistic performance of ceramic-faced light armor systems can be predicted with two simple parameters. Parameters are dimensionless and only require available material and structural properties. Performance can be predicted with Hugoniot elastic limit as characteristic strength term. Dimensionality of parameter space can be reduced but still remain relevant to inherent mechanics. Abstract: Two dimensionless parameters are proposed to give first-order approximations for the ballistic performance of ceramic-faced bicomponent armor plates impacted by conical-nosed steel projectiles. The current work collates expansive experimental data from Wilkins and Mayseless covering a broad range of material and mechanical properties, target construction, and projectile dimensions, the data is collapsed using the Hugoniot elastic limit of the ceramic strike face as a strength metric. Within datasets where experimental conditions are kept constant, a singular cubic curve can be generated, but variations in experimental conditions for the ballistic limit test between datasets can result in differences in the predictive curve coefficients.